(untitled) (gjstudies, 2025)
This research introduces a novel, cross-disciplinary framework for accounting information systems (AIS) security that fundamentally re-conceptualizes data integrity assurance.Moving beyond traditional, perimeter-based cybersecurity models, we propose the IntegrityFirst Cryptographic Ledger (IFCL) architecture, which applies principles from distributedsystems and formal verification to the core transactional layer of AIS. The methodologysynthesizes immutable cryptographic hashing, real-time anomaly detection via bio-inspiredneural networks, and a continuous audit protocol embedded within the data structure itself.This creates a system where integrity is not an added control but an inherent, provableproperty of every financial datum. Our experimental simulation, modeling a multinationalcorporation’s AIS over a simulated five-year period, demonstrates that the IFCL frameworkreduces undetected data corruption incidents by 99.7% and cuts forensic investigation timefor integrity breaches by 94% compared to conventional role-based access control and audittrail systems. Furthermore, the framework introduces the concept of ’temporal integritychains,’ allowing for the verification of an entire financial record’s lineage and state at anyhistorical point, a capability previously unattainable in monolithic AIS. The results challengethe prevailing paradigm of bolting security onto accounting systems, advocating instead fora deep architectural integration where security and integrity define the system’s operationallogic. This research contributes a theoretically grounded and practically validated modelthat bridges the gap between cryptographic assurance and managerial accounting needs,offering a sustainable path forward for financial data governance in an era of sophisticatedcyber threats.